Interactive matrix website: Facilitating discovery learning to improve students' mathematical literacy skills - Eugenia Natalia Lawang; Sri Andayani (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
This research is motivated by the low mathematical literacy skills of students in Indonesia, which is an important skill for the application of mathematics in daily life. The purpose of this study is to develop an interactive website based on google sites to improve students' mathematical literacy skills, especially in matrix materials. The method used in this study is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which involves students of grade XI social studies in Yogyakarta as participants. Data is collected through tests (pre-test and post-test) and non-tests (questionnaires and observations) to get a comprehensive picture of the effectiveness of the website developed. Data analysis is carried out qualitatively and quantitatively to assess the validity, practicality, and effectiveness of the product. The results of the study showed that the website developed met the validity criteria of material and media experts, and was considered very practical by teachers and students, with an average learning implementation of 90.25%. The effectiveness test using the paired sample t-test showed a significant increase between the pre-test and post-test scores, with the average post-test reaching 84.84, which exceeded the minimum completeness criteria (KKTP) set. In addition, more than 75% of students have successfully achieved KKTP. The implication of this study is that the interactive website developed can be an effective tool in improving students' mathematical literacy skills, so it is expected to help students better understand mathematical concepts and apply them in daily life. This research makes a positive contribution to efforts to improve the quality of mathematics education in Indonesia